2007
DOI: 10.1016/j.bmc.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-inflammatory actions of the elmiric (lipoamino) acids

Abstract: A library of amino acid-fatty acid conjugates (elmiric acids) was synthesized and evaluated for activity as potential anti-inflammatory agents. The compounds were tested in vitro for their effects on cell proliferation and prostaglandin production and compared with their effects on in vivo models of inflammation. LPS stimulated RAW 267.4 mouse macrophage cells was the in vitro model and phorbol ester-induced mouse ear edema served as the principal in vivo model. The prostaglandin responses were found to be str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…*i denotes immunoreactive. The data shown were previously reported in Burstein et al (2007). P<0.05 by ANOVA vs. the oil control.…”
Section: The Elmiric Acidssupporting
confidence: 79%
See 3 more Smart Citations
“…*i denotes immunoreactive. The data shown were previously reported in Burstein et al (2007). P<0.05 by ANOVA vs. the oil control.…”
Section: The Elmiric Acidssupporting
confidence: 79%
“…Luminometer units are directly proportional to the number of metabolically active cells and are a measure of ATP levels. The data shown were previously reported in Burstein et al (2007). All of the ratio values greater than 20 are significant at the 95% confidence level when compared to the DMSO-LPS control by ANOVA.…”
Section: The Elmiric Acidssupporting
confidence: 59%
See 2 more Smart Citations
“…Based on in vitro and in vivo studies, amino acid-based surfactants may offer use in pharmaceutical, skin care and cosmetic applications due to their lower irritancy potential, less toxic and high biodegradability 41,42 . Lipoamino acids were used as potential anti-inflammatory agents 43 . Gopal et al 44 reported the cytotoxicity of series of N-sapienoyl C 16:1 amino acids and among those N-sapienoyl leucine exhibited the higher activity towards the selective tumor cell lines.…”
Section: In Vitro Cytotoxicity Assessmentmentioning
confidence: 99%